Multi pigment meter for advanced agricultural and environmental monitoring - Meena, Vijay Singh; Meena, Sunita Kumari; Bhat, Verender (Indian Farming, 2024)
The multi pigment meter is an advanced tool designed for precise agricultural and environmental monitoring. It measures chlorophyll and other plant pigments, providing vital insights into plant health and stress levels. This technology is crucial for optimizing crop management, enabling early detection of issues like nutrient deficiencies and disease. By integrating GPS, it offers precise geolocationof data, supporting precision farming practices. This ensures efficient use of resources, enhances crop yield, and promotes sustainable agriculture. Its application extends to environmental monitoring, aiding in the conservation and study of natural vegetation and ecosystems.